PENGARUH MEDIA PEMBELAJARAN SNAKE LADDER TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Dwi Cahyono Saputra; Dhina Cahya Rohim; Devy Aufia Abshor (STKIP Subang, 2026)
Media on mathematics learning outcomes of elementary school students. The research method used was quantitative quasi experimental design type with a nonequivalent control group design. The sampling technique uses purposive sampling. The sample consisted of two classes with a total of 30 students, namely grade III SD 3 Adiwarno as an experimental class of 17 students and SD 4 Adiwarno as a control class of 13 students. Data collection techniques through interviews, tests, questionnaires, and documentation. The test is in the form of pretest and posttest questions given in both classes. The results of the study included data analysis techniques which included normality tests using the Shapiro Wilk method, homogeneity tests, t-tests, N-Gain tests, and analysis of student responses using the Likert Scale. Based on the results of the independent sample t-test, a sig value was obtained. (2-tailed) of 0.000 < 0.05, then H0 is rejected and Ha is accepted. The average posttest score of the experimental class that used the Snake Ladder learning media was 85.29, higher than the control class that used learning of 71.54. Supported by the results of the Paired sample t-test obtained with a sig value. (2-tailed) of 0.000 < 0.05, then H0 is rejected and Ha is accepted. The average pretest score of the experimental class was 48.82 and the average posttest score showed 85.29, which shows a significant increase. Based on the results of the study, it can be concluded that the use of Snake Ladder learning media has a positive influence or impact on the learning outcomes of mathematics of data presentation materials in tables in elementary schools.